Application of generalised hierarchical product of graphs for computing F-index of four operations on graphs - Nilanjan De (Indonesian Combinatorial Society (InaCombS), 2018)
The F-index of a graph is defined as the sum of cubes of the vertex degrees of the graph which was introduced in 1972, in the same paper where the first and second Zagreb indices were introduced. In this paper we study the F-index of four operations on graphs which were introduced by Eliasi and Taeri, and hence using the derived results we find F-index of some particular and chemically interesting graphs.